Pupal diapause termination in Bactrocera minax: An insight on 20-hydroxyecdysone induced phenotypic and genotypic expressions - Zhenzhong Chen (2018)
The Chinese citrus fruit fly, Bactrocera minax, is an economically important pest of citrus. It exhibits pupal diapause from November to May to combat harsh environmental conditions. Such a long pupal diapause is a barrier for laboratory rearing and development of control strategies against this pest. In the present study, 20-hydroxyecdysone (20E) was used to break pupal diapause of B. minax by topical application. After diapause termination by 20E treated, the pupal ontogenetic processes were observed along the temporal trajectory. The pupal response time to 20E was estimated by detecting the relative expression of 20E responsive genes at different times after 20E-treatment. Results revealed that 20E could effectively terminate the pupal diapause in a dose-dependent manner and significantly shorten the time for 50% adult emergence (Et 50). 20E response genes, including ecr, broad and foxo, were up-regulated within 72h, indicating these genes are involved in pupal metamorphosis and diapause termination processes. Morphological changes showed the pupal metamorphosis began ∼7 days after 20E-treatment at 22 °C. This study does not only pave the way for artificial rearing in the laboratory through manipulating of pupal diapause termination, but also deepens our understanding of the underlying pupal diapause termination mechanism of B. minax.